Mobile Marketing in the Pharmaceutical Industry: Benefits, Costs and Risks - Nofal, Hani (2011)
The project will to look into the increasing trend for the mobile marketing worldwide and in particular the pharmaceutical industry. Afterwards will identify the list of the major benefits that can drive revenue for the pharmaceutical companies. Then, a costing analysis will be initiated to evaluate the budget of implementing such initiatives by exploring the type of cost of implementing such tools and giving specific case analysis for implementing Smartphone apps for Pfizer within for the coming two years. Finally there will be dissuasion on the list of risks and challenges that might face such initiatives.